2003
DOI: 10.1038/sj.bmt.1704113
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell transplantation after salvage therapy with high-dose cytarabine and amsacrine in adults with high-risk leukaemia

Abstract: Summary:Stem cell transplantation (SCT) may be the only curative option for patients with relapsed or refractory leukaemia, that is, high-risk (HR) leukaemia. Several salvage regimens have been used to cytoreduce disease before SCT, but disease progression or treatment toxicity limits numbers of patients receiving SCT. Here, we report our experience with high-dose cytarabine and amsacrine (Araamsa) to salvage patients with HR-leukaemia in the context of SCT. A total of 34 patients with HR-leukaemia (20 AML, 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Nor is there evidence that altering the schedule of re‐induction therapy (timed‐sequential therapy) is of value (Yin et al , 2001). A number of small studies have shown encouraging results with combinations of high‐dose Ara‐C and amsacrine (Jehn & Heinemann, 1990; MacCallum et al , 1993; Tauro et al , 2003) and this regimen requires further validation in phase 3 studies. The benefit of P‐gp inhibition in patients with relapsed AML remains controversial.…”
Section: Salvage Options In Patients With Relapsed Amlmentioning
confidence: 99%
“…Nor is there evidence that altering the schedule of re‐induction therapy (timed‐sequential therapy) is of value (Yin et al , 2001). A number of small studies have shown encouraging results with combinations of high‐dose Ara‐C and amsacrine (Jehn & Heinemann, 1990; MacCallum et al , 1993; Tauro et al , 2003) and this regimen requires further validation in phase 3 studies. The benefit of P‐gp inhibition in patients with relapsed AML remains controversial.…”
Section: Salvage Options In Patients With Relapsed Amlmentioning
confidence: 99%
“…In addition, amsacrine in combination with etoposide and high-dose methylprednisolone was used as salvage therapy for relapsed and refractory ALL with moderate treatment-related morbidities. [8][9][10][11][12][13] Based on these results, we introduced amsacrine, etoposide, and high-dose methylprednisolone as a new add-on treatment element for primary high-risk ALL.…”
Section: Introductionmentioning
confidence: 99%
“…Amsacrine demonstrated promising efficacy in mostly adult patients with refractory acute myeloid leukemia (AML) when combined with etoposide or cytarabine. In addition, amsacrine in combination with etoposide and high‐dose methylprednisolone was used as salvage therapy for relapsed and refractory ALL with moderate treatment‐related morbidities 8–13 . Based on these results, we introduced amsacrine, etoposide, and high‐dose methylprednisolone as a new add‐on treatment element for primary high‐risk ALL.…”
Section: Introductionmentioning
confidence: 99%